Confucianism and democratization in East Asia - Sin, To-ch'ol. (New York : Cambridge University Press, 2012)
"This book examines how Confucianism affects the development of demo cratic citizenship in East Asia. To what extent do East Asians remain a ttached to the particular way of life and system of government that Con fucius and Mencius advocated to bring about a community of grand harmon y? How does such attachment to Confucian civic norms affect their engag ement in civic affairs? How does attachment to Confucian paternalistic meritocracy affect their commitment to democracy? The book addresses th ese question in the context of public opinion surveys conducted in East Asia and other regions"--Provided by publisher.
The evolution of Confucian East Asia and its cultural legacies -- Th e Confucian Asian values thesis: theoretical debate and empirical resea rch -- Confucianism as a hierarchical way of life -- Confucianism as a government of paternalistic meritocracy -- Communitarianism and civic a ctivism -- Familism and civic orientations -- Conceptions of democracy -- Support for democracy -- Reassessing the Confucian Asian values deba te.
Includes bibliographical references and index.
Keywords: Democratization -- East Asia; Democracy -- East Asia; Confucianism and state -- East Asia